Kedudukan Undang-Undang Perkawinan terhadap Perkawinan Beda Agama di Luar Negeri - Arianty Anggraeny Mangarengi; Yuli Adha Hamzah (SIGn Jurnal Hukum, 2021)
This study aims to determine the position and authority of Law No. 16 of 2019 in responding to interfaith marriages abroad. The type of legal research used is a dogmatic juridical research method. The data collection in this study was carried out through a literature study of laws and regulations, journals, research results, and books. This study uses hermeneutic analysis and interpretation methods to analyze the data used in this study. The study results show that interfaith marriage is not justified in all scriptures recognized in Indonesia. Couples who want to have interfaith marriages can hold them abroad. Meanwhile, from the state’s point of view, interfaith marriages are inconsistent. In this case, Law No. 16 of 2019 does not justify interfaith marriage, while Law No. 24 of 2013 can determine the marital status of interfaith abroad. So that the legal certainty of interfaith marriages is not based on Law No. 16 of 2019 but Law No. 24 of 2013. Therefore, it is suggested that the government amend Law No. 16 of 2019. In this case, it contains norms that legitimize interfaith marriages as regulated in Law No. 24 of 2013. If Law No. 16 of 2019 is considered still relevant to the socio-cultural conditions of Indonesia, the government must amend Law No. 24 of 2013. In this case, it is removing norms that legitimize interfaith marriages. The amendments to the legislation attempt to resolve inconsistencies in the legislation related to interfaith marriages.